2005
DOI: 10.1128/aac.49.11.4763-4766.2005
|View full text |Cite
|
Sign up to set email alerts
|

AmpC and OprD Are Not Involved in the Mechanism of Imipenem Hypersusceptibility among Pseudomonas aeruginosa Isolates Overexpressing the mexCD - oprJ Efflux Pump

Abstract: Pseudomonas aeruginosa strains that overexpress mexCD-oprJ become hypersusceptible to imipenem. Disruption of AmpC induction has been suggested to cause this phenotype. However, data from this study demonstrate that hypersusceptibility to imipenem can develop without changes in ampC expression or AmpC activity. Furthermore, hypersusceptibility is not caused by changes in expression of the outer membrane porin, OprD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
3
25
0
Order By: Relevance
“…Although other investigators have suggested that imipenem hypersusceptibility is a result of disrupted ampC induction (151), the observation VOL. 22,2009 ANTIBACTERIAL-RESISTANT PSEUDOMONAS AERUGINOSA 601 that AmpC overproduction does not significantly increase imipenem MICs (63,131,169,274) argues against this hypothesis. Furthermore, our own studies have shown that imipenem-hypersusceptible mutants can be selected from P. aeruginosa parent strains that are partially and fully derepressed for ampC expression, without any changes in either the expression of ampC or AmpC hydrolysis activity (274).…”
Section: Mexcd-oprj Overproduction and Hypersusceptibility To Antibacmentioning
confidence: 69%
See 3 more Smart Citations
“…Although other investigators have suggested that imipenem hypersusceptibility is a result of disrupted ampC induction (151), the observation VOL. 22,2009 ANTIBACTERIAL-RESISTANT PSEUDOMONAS AERUGINOSA 601 that AmpC overproduction does not significantly increase imipenem MICs (63,131,169,274) argues against this hypothesis. Furthermore, our own studies have shown that imipenem-hypersusceptible mutants can be selected from P. aeruginosa parent strains that are partially and fully derepressed for ampC expression, without any changes in either the expression of ampC or AmpC hydrolysis activity (274).…”
Section: Mexcd-oprj Overproduction and Hypersusceptibility To Antibacmentioning
confidence: 69%
“…Although data from our own studies also showed decreased induction of ampC expression associated with overexpression of mexCD-oprJ (274), this association was observed only in isogenic mutants from a clinical isolate with wild-type ampC expression. When the parent strains were derepressed for ampC expression, overexpression of mexC was not associated with any change in ampC expression among the isogenic mutants selected (274).…”
Section: Mexcd-oprj Overproduction and Hypersusceptibility To Antibacmentioning
confidence: 85%
See 2 more Smart Citations
“…MBLs are reported to be resistant to all β-lactam antibiotics except for Monobactams such as Aztreonam (9,19). In this study, 96.87% of the isolates were resistant to aztreonam, suggesting coexistence of other resistance mechanisms such as AmpC type β-lactamases or MexAB-OprM Efflux Pumps (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%